RETRACTED ARTICLE: Design of a real-time health monitoring and prediction system for table tennis players based on optical detection sensor networks - Dehua, Liu (Optical and quantum electronics, 2024)
With the popularization and development of table tennis, the demand for health management and exercise status monitoring of table tennis players is increasing day by day. However, most of the current table tennis player health monitoring systems are based on traditional sensor technology, which has problems of complexity and high maintenance cost. The aim of this study is to design a real-time health monitoring and prediction system for table tennis players based on optical sensor network. In this study, optical sensors were used as monitoring means to measure the temperature, heart rate and movement posture of table tennis players, and to analyze the changes of physiological parameters of table tennis players in different training environments. At the same time, the optical detection sensor network is designed and implemented for real-time monitoring and data collection of table tennis players. Through experiments and data analysis, the system can accurately and real-time monitor and predict the health status of table tennis players. The system can detect the fatigue level, abnormal heart rate and wrong posture of table tennis players in time, and provide corresponding warnings and suggestions.